'We would have missed out so much had we terminated': What fathers of a child with Down syndrome think about current non-invasive prenatal testing for Down syndrome. (September 2019) - How, Bethea; Smidt, Andy; Wilson, Nathan J; Barton, Rebecca; Valentin, Chelsea
Non-invasive prenatal testing (NIPT) allows early, accurate diagnosis of Down syndrome that has resulted in increased terminations. This qualitative study involved in-depth interviews of fathers of children with Down syndrome about their views on the availability of NIPT. Thematic network analysis revealed that although fathers appreciated an early diagnosis with NIPT, they saw the test as being a predetermined pathway to termination. Fathers felt that expectation to terminate reflects negative societal attitudes towards those with Down syndrome and disability, fearing that NIPT may become a form of eugenics. Fathers retrospectively contrasted these attitudes with the actual reality of raising their children with Down syndrome, which they described as bringing joy to their lives. Findings suggest that although fathers valued NIPT as an information-giving tool that allowed autonomous parental choices about the pregnancy, they believe that it should be accompanied by balanced information about the reality of raising a child with Down syndrome.